2008
DOI: 10.1248/bpb.31.1530
|View full text |Cite
|
Sign up to set email alerts
|

Total Ginsenosides Inhibit the Right Ventricular Hypertrophy Induced by Monocrotaline in Rats

Abstract: Ginseng, the root of Panax ginseng C. A. MEYER, is a wellknown and popular herbal medicine used in China for centuries and is now a world wide used natural medicine. Ginsenosides, the pharmacologically active components found in Ginseng, are also found in the leaf and stem of Panax ginseng C. A. MEYER, 1) and more than 30 different ginsenosides have been isolated from Ginseng. Ginsenosides exert various pharmacological effects on the central nervous, cardiovascular, endocrine, and immune systems.2-4) Notably, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 23 publications
(21 reference statements)
1
26
0
Order By: Relevance
“…Over the past decades, researchers have focused on defining the specific mechanism by which ginseng exerts its cardioprotective effects, especially its unique action in I/R injury (Liu et al, 2002;Qin et al, 2008). Although experimental studies have suggested that some ginsenosides play roles in cardioprotection against I/R injury, in clinical usage, ginseng is usually combined with other herbs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past decades, researchers have focused on defining the specific mechanism by which ginseng exerts its cardioprotective effects, especially its unique action in I/R injury (Liu et al, 2002;Qin et al, 2008). Although experimental studies have suggested that some ginsenosides play roles in cardioprotection against I/R injury, in clinical usage, ginseng is usually combined with other herbs.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulated evidence has showed a connection between the action of ginseng and the MAPKs pathway. For example, compound K significantly repressed the PMA-mediated activation of p38 MAPK, Erk and JNK (Jung et al, 2006); total ginsenosides attenuated monocrotaline-induced right ventricle hypertrophy through suppressing activated Erk (Qin et al, 2008); ginsenoside Rd protected and rescued rat intestinal epithelial cells from irradiation-induced apoptosis through a pathway requiring inactivation of MEK (Tamura et al, 2008); ginsenoside Re reduces insulin resistance in 3T3-L1 adipocytes and high-fat diet rats through inhibition of JNK (Zhang et al, 2008). However, the role of the MAPKs pathway in ginseng's cardioprotective effects still remains unclear.…”
Section: Introductionmentioning
confidence: 98%
“…It has been reported that the expressions of mRNA and/or protein of calcineurin (CaN) and the expression of mRNA of extracellular signal-regulated kinase-1 (ERK-1) from RVs in MCT-treated rats are significantly increased. 27,28) CaN and ERK signal pathways are known to be key mediators of cardiac hypertrophy. Therefore, whether GCIP-27 plays an important role on the repress of some key signal transduction pathways such as CaN signaling and ERK signaling in RV hypertrophy need more study in our future works.…”
Section: Discussionmentioning
confidence: 99%
“…4 Moreover, ginseng has been demonstrated to attenuate right and left ventricular hypertrophy in a number of experimental models. [5][6][7] Because the underlying basis for the antihypertrophic effect of ginseng is poorly understood, we studied the mechanisms for the antihypertrophic effect of ginseng using cultured ventricular myocytes and an in vivo model of heart failure secondary to chronic ischemia. The study centered primarily on the Na ϩ -H ϩ exchanger-1 isoform (NHE-1), which has been extensively shown to contribute to hypertrophy and heart failure.…”
mentioning
confidence: 99%